Current Status of Birth Registration Practice in Nepal - Kafle, Rameshwor (Baneshwor Campus Journal of Academia, 2024)
Birth registration is an essential element of civil registration and vital statistics which provide a legal identity and recognize the rights of an individual. In Nepal, birth registration has a long history starting from the Village Panchayat Act 1962 which was the first act with a provision for a birth certificate. Despite the over half-century experience of birth registration efforts, challenges to universal birth certificate coverage remain present, especially among the rural population. This research will investigate the current practices of birth registration in Nepal based on the findings of the National Population and Housing Census 2021. The analysis will show respective rates of birth certificate issuance across the regions, provinces, and development districts. Some areas show remarkable success in birth registration, while others struggle to reach significant coverage levels. The experience shows the critical role of government responsiveness to the development of birth registration which is especially important for rural areas and districts with significant rural populations. In this light, targeted efforts and outreach campaigns are necessary to eliminate barriers, thus guaranteeing equal access to birth registration for all children in Nepal.